COVID-19 Poetry in Ireland: Reflections on Lockdown in Celia de Fréine’s Léaslíne a Lorg / In Search of a Horizon - Luz Mar González-Arias (Estudios Irlandeses, 2024)
This article looks critically at Celia de Fréine’s Léaslíne a Lorg / In Search of a Horizon (2022), a poetry collection entirely devoted to the lockdown experienced during the first wave of the COVID-19 pandemic by an Irish woman – easily identified with the poet herself – from her house in Dublin. In the 18 poems that make up the collection, published in bilingual format (English and Irish), de Fréine addresses issues as relevant as the supposed objectivity of the scientific discourse around the virus, the human-nonhuman connection, environmental damage and the historical links of the COVID-19 pandemic with previous health crises lived through in Ireland, specifically the Hepatitis C Scandal. My analysis will close-read the poems, adopting both a national and a transnational perspective. The ultimate aim of this essay is to look at the virus in its socio-cultural dimension in order to complement the biomedical narratives around it.